How Much Do the Affective Factors Contribute to Writing Performance?: A Path Analysis Study of Chained Predictors - Nurul Hidayah Pratama; Ekaning Dewanti Laksmi; Enny Irawati (Pascasarjana UM, 2018)
Abstract: Affective aspects are considered as one of the most influencing factor in learning foreign language. The aim of this study is to figure the model of affective aspects as factors in predicting writing performance of the EFL college students. The sample of this study consists of 134 students of English Department, UIN Maulana Malik Ibrahim. The result of this study confirms that writing anxiety, writing self-efficacy, and writing attitude contribute to and writing performance (39.2%). Also, their attitude towards writing is more likely influenced by how they perceived their self-efficacy towards writing activities rather that their anxiety (12.5%). The findings reveals that self-efficacy and attitudes matter in doing writing tasks and students who have a low level of attitudes are caused by how they perceive their own self-efficacy. Writing anxiety level is not the most predictive factor in determining students’ writing performance.Key Words: writing anxiety, writing self-efficacy, writing attitudes, writing performance, affective factorsAbstrak: Aspek afektif dianggap sebagai salah satu faktor yang paling berpengaruh dalam belajar ba-hasa asing. Tujuan dari penelitian ini adalah untuk mengetahui model aspek afektif sebagai faktor dalam memprediksi kinerja penulisan mahasiswa jurusan bahasa Inggris. Sampel penelitian ini terdiri dari 134 siswa Jurusan Bahasa Inggris, UIN Maulana Malik Ibrahim. Hasil penelitian ini menegaskan bahwa kecemasan, efikasi diri, dan sikap menulis berkontribusi terhadap kemampuan menulis (39,2%). Selain itu, sikap terhadap kegiatan menulis cenderung dipengaruhi oleh bagaimana mereka menilai efikasi diri mereka terhadap aktivitas menulis, bukan kecemasan mereka (12,5%). Temuan ini menunjukkan bahwa efikasi diri dan sikap berpengaruh dalam melakukan menulis dan siswa yang memiliki sikap yang ku-rang positif disebabkan oleh bagaimana mereka yakin pada kemampuan mereka sendiri. Selain itu, kecemasan bukanlah faktor yang paling prediktif dalam menentukan kinerja menulis.Kata kunci: kecemasan menulis, efikasi diri menulis, sikap menulis, kinerja menulis, faktor afektif